Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa - Davis, Adrian L.v.; Deschodt, Christian M. (Zootaxa, 2018)
Two new, putative, closely-related species of dung beetles are described in the genus Garreta Janssens, 1940 (tribe Gymnopleurini). Garreta australugens new species, is known from various dung types in the southeast lowlands of Africa (validated for South Africa, Mozambique and Zimbabwe with a probable record from Botswana). It is, here, separated at species level from its putative closest relative, Garreta lugens (Fairmaire, 1891), recorded from the lowlands of northeast Africa (validated for Kenya with additional records from Ethiopia, Somalia and Tanzania). These two taxa were formerly considered to comprise a single species. All specimens in the type series of Garreta namalugens new species, were recorded at low altitude in arid, rocky mountains from west central to northwest Namibia, mostly on dung in communal middens of the Rock Hyrax (Procavia capensis (Pallas, 1766)).